2021
DOI: 10.1186/s13287-021-02656-4
|View full text |Cite
|
Sign up to set email alerts
|

PINK1 deficiency impairs osteoblast differentiation through aberrant mitochondrial homeostasis

Abstract: Background PTEN-induced kinase 1 (PINK1) is a serine/threonine-protein kinase in mitochondria that is critical for mitochondrial quality control. PINK1 triggers mitophagy, a selective autophagy of mitochondria, and is involved in mitochondrial regeneration. Although increments of mitochondrial biogenesis and activity are known to be crucial during differentiation, data regarding the specific role of PINK1 in osteogenic maturation and bone remodeling are limited. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 72 publications
1
21
0
Order By: Relevance
“…Growing evidence has indicated that UCHL1 could function via inhibiting mitophagy (Cerqueira et al 2020; Ham et al 2021), which is a positive regulator of osteogenesis (Pei et al 2018; Lee et al 2021). Hence, we explored whether mitophagy was involved in the UCHL1-regulated osteogenesis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Growing evidence has indicated that UCHL1 could function via inhibiting mitophagy (Cerqueira et al 2020; Ham et al 2021), which is a positive regulator of osteogenesis (Pei et al 2018; Lee et al 2021). Hence, we explored whether mitophagy was involved in the UCHL1-regulated osteogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…Mechanistically, we have demonstrated that UCHL1 suppressed PDLSC osteogenesis through inhibiting mitophagy in periodontitis-associated inflammation. Mitophagy, anorganelle-specific autophagy pathway to remove dysfunctional or superfluous mitochondria (Palikaras et al 2018), has been recently identified as a critical role in osteogenesis, with numerous studies reporting that the activation of PINK1/Parkin-mediated mitophagy was a requisite in osteogenic differentiation (Pei et al 2018; Lee et al 2021). This corresponded to our results of the effects of mitophagy inhibitor on PDLSC osteogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Lee ( 53 ) found that PINK1 expression was reduced in OP patients. Bone mass was significantly reduced in an ovariectomized mouse model with PINK1 gene deficiency.…”
Section: The Pathological Role Of Mitochondria In Osteoporosismentioning
confidence: 99%
“…Accumulating evidence suggests that aberrant mitophagy plays a key role in stem cell differentiation and in bone metabolism disorders [ 12 , 118 ]. Recent studies have found that mitophagy is involved in the regulation of OP [ 119 , 120 ], which may be related to signals such as phosphoinositide 3-kinase (PI3K) [ 115 ] and Pink1 [ 121 ] (as shown in Figure 2 ).…”
Section: Mitophagy and Osteoporosismentioning
confidence: 99%
“…Activation of PINK1 is necessary during osteoblast differentiation, which is associated with mitochondrial quality control and low reactive oxygen species production. Lee et al [ 121 ] found that the expression of endogenous PINK1 is increased during osteogenic differentiation. Downregulation of PINK1 impairs mitochondrial homeostasis, increases mitochondrial ROS generation, and inhibits osteoblast differentiation.…”
Section: Mitophagy and Osteoporosismentioning
confidence: 99%